Low-dose curcuminoid-loaded in dextran nanobubbles can prevent metastatic spreading in prostate cancer cells. (13th March 2019) - Bessone, F; Argenziano, M; Grillo, G; Ferrara, B; Pizzimenti, S; Barrera, G; Cravotto, G; Guiot, C; Stura, I; Cavalli, R; Dianzani, C
Abstract: Preventing recurrences and metastasis of prostate cancer after prostatectomy by administering adjuvant therapies is quite a controversial issue. In addition to effectiveness, absence of side effects and long term toxicity are mandatory. Curcuminoids (Curc) extracted with innovative techniques and effectively loaded by polymeric nanobubbles (Curc-NBs) satisfy such requirements. Curc-NBs showed stable over 30 d, were effectively internalized by tumor cells and were able to slowly release Curc in a sustained way. Significant biological effects were detected in PC-3 and DU-145 cell lines where Curc-NBs were able to inhibit adhesion and migration, to promote cell apoptosis and to affect cell viability and colony-forming capacity in a dose-dependent manner. Since the favourable effects are already detectable at very low doses, which can be reached at a clinical level, the actual drug concentration can be visualized and monitored by US or MRI, Curc-NBs can be proposed as an effective adjuvant theranostic tool.